Prosfek Penumbuhan Wirausahawan Muda Pertanian (PWMP) Di Pulau Lombok - Tajidan Tajidan; Efendy Efendy; Halil Halil; Edy Fernandez (Jurnal Gema Ngabdi, 2019)
The objectives of the community service are:  maintaining the alumni commitment as agricultural young entrepreneurs;  increase the capacity and ability of alumni in the management of business in agriculture;  increasing the business scale by adding the ability to finance agribusiness businesses; and developing business networks (net-working) and financing and marketing cooperation. The output expected as an output of this service activity is an article published in national or international journals. To achieve the purpose of this service, it is carried out with a coaching and mentoring approach. Coaching is done by the focus group discussion (FGD) method, training with the agribusiness field school method, and mentoring in the problem solving method. From a series of implementation activities can be summarized as follows: the commitment of alumni as young agricultural entrepreneurs is still able to be held which is shown by the still strong spirit and entrepreneurial spirit; (the alumni who are members of the PWMP Group have the ability to increase the capacity of business management in agriculture, including 3 (three) of the 7 (seven) PWMP groups that have opened business branches and appointed employees to assist production activities and services to customers; in general there has been an increase in the ability of financing sourced from an average allowance for operating results of 18.3% from November 2017 to July 2018 or 2.29% / month; and the development of business networks and marketing is still an obstacle for most young agricultural entrepreneurs, except the PWMP Bintang Tani Group which has a business network and regular customers in the marketing aspect.